Особенности создания газотурбинной установки регенеративного цикла для ГПА - Романов, В. В.; Спицын, В. Е.; Боцула, А. Л.; Мовчан, С. Н.; Чобенко, В. Н. (Eastern-European Journal of Enterprise Technologies, 2009)
Features of cycle parameters choice and general design recuperative cycle gas turbine unit for gas pump-line set are presented. Brief descriptions of the GT and recuperator design are shown